2020
DOI: 10.1002/lsm.23263
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of CO2 Laser Treatment for Sexual Function and Vaginal Laxity Improvement in Pre‐Menopausal Women

Abstract: Background and Objectives Vaginal laxity lacks standardized diagnosis and severity criteria. It is considered as a subjective complaint that reflects decreased sexual satisfaction due to vaginal loosening. Treatment modalities have included physiotherapy and plastic surgery. Recently, laser treatments have also gained popularity as a means of relieving gynecological complaints such as pelvic organ prolapse, stress urinary incontinence, and genitourinary syndrome of menopause. The aim of the current study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Despite the improvement being significant in all clinical outcomes, the main improvement was found in VuHI, which appears as a further novel finding. This finding makes fractional microablative CO 2 laser as an effective tool for vulvar symptoms and signs of GSM, as well as for vaginal ones (as reported in previous studies and also confirmed by our results [14,16,19–23,40–44]). Other major improvements were observed for dyspareunia, vaginal dryness, reduced sensitivity during sexual intercourse, and vulvodynia.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the improvement being significant in all clinical outcomes, the main improvement was found in VuHI, which appears as a further novel finding. This finding makes fractional microablative CO 2 laser as an effective tool for vulvar symptoms and signs of GSM, as well as for vaginal ones (as reported in previous studies and also confirmed by our results [14,16,19–23,40–44]). Other major improvements were observed for dyspareunia, vaginal dryness, reduced sensitivity during sexual intercourse, and vulvodynia.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the heavier atrophy related to burning, dyspareunia on vaginal opening, and lower one‐third of the vagina could be markedly improved [14]. So, based on these changes, the urinary symptoms and sexual function and vaginal laxity were significantly effect in the intravaginal fractional CO 2 laser groups [28,29], which laser group showed a statistically significant reduction in nocturia compared with that of the promestriene group [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been some studies evaluating the efficacy of CO 2 laser treatment in women with a lack of sexual interest due to vaginal laxity, which shows a statistically significant short‐term effect (≤6 months) on women's sex life [27]. An interesting randomized clinical study was performed by Aguiar et al [28] showing the superior influence of fractional intravaginal CO 2 laser treatment on symptoms of OAB and nocturia in comparison with vaginal lubricant and topical estrogen (promestriene).…”
Section: Discussionmentioning
confidence: 99%